Medicinal plants in Inamberi Research Station of Manokwari and their conservation status - Khayati, Lisna; Julanda Noya; Nithanel M. H. Benu; Freddy Jontara Hutapea (Talenta Publisher, 2023)
Papua is well-known for its medicinal plants. However, several of them are not well documented yet. Numerous efforts have recently been addressed to record medicinal plants in different parts of Papua. This study aimed to identify medicinal plants in the Inamberi Research Station of Manokwari, West Papua Province. All plant species grown in the research station were listed and documented. The method used in this study was the observation method with survey techniques. Literature reviews were performed to identify the medicinal plants that were generally used by the local people of Papua. The conservation status of medicinal plants was derived from the IUCN red list website. The total medicinal plants grown in the research station were about 43 species, dominated by Euphorbiaceae and Moraceae families. Trees were the dominant medicinal plants. Medicinal plants in the research station can treat various diseases and some of them can cure more than one disease. Local people of Papua generally utilize leaves as medicinal plants. The utilization of medicinal plants was simple: boiling and drinking, directly eating it, chewing and attaching it to the wounds, and rubbing it on the skin. The conservation status of medicinal plants was categorized as low risk. However, concern should be given to Pterocarpus indicus that has been categorized by IUCN as an Endangered species. Ex situ and in situ conservation are required to protect this species